Effects of oxalate intake on calcium and phosphorus balance in bulls fed Napier - Das, NG; Huque, KS; Alam, MR; Sultana, N; Amanullah, SM (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted to examine the effects of oxalate intake on calcium and phosphorus balance in bulls fed Napier silage. Eighteen growing bulls having average live weight of 249 ± 8.38 Kg and aged about 40 months were divided into three groups of six animals in each group. They were assigned to dietary treatments T0 (considered as control), T1 and T2 consisting of rice straw, rice straw and Napier silage (1:1, DM basis) and Napier silage ad libitum, respectively for a period of 21 days. A concentrate mixture composed of 940 g wheat bran, 60g dicalcium phosphate (DCP) and 50g common salt was fed to each bull at the rate of 1.05 Kg/d. With the increase of Napier silage intake there was a significant (P<0.01) increase of oxalate intake (17.91, 24.65 and 30.97 g/d, with T0, T1 and T2 diets, respectively) with the subsequent increase of (P<0.01) their excretion through feces (3.02, 8.66 and 11.02 g/d, respectively). The fecal and urinary excretion of calcium (11.41, 18.25 and 25.28 g/d, respectively) and phosphorus (13.37, 16.85 and 20.09 g/d, respectively) of the animals fed different diets were significantly (P<0.05) high when the straw diet was replaced with 50 and 100 % Napier silage, respectively and there were calcium and phosphorus deficiencies in bulls fed Napier silage. Thus, Napier silage diets brought about a significant (P<0.05) reduction in calcium (12.19, 6.87 and 1.36 g/d, respectively) and phosphorus (7.17, 6.40 and 5.39 g/d, respectively) balances though the intake of these two minerals were adequate showing linear reverse relationship with the increase of oxalate intake from Napier silage. Key words: Napier silage; Oxalate; Calcium; Phosphorus; Bull DOI: http://dx.doi.org/10.3329/bjas.v39i1-2.9677 Bang. J. Anim. Sci. 2010, 39(1&2): 58-66